Socio Familial Factor’s Impact on Educational Achievement - Wasim Ullah; Munir Ahmed; Zainab Anfal; Masood Ahmed (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
In many developing countries, like Pakistan, providing even basic necessities can be a challenge, let alone luxuries like access to the latest technologies. Given the socio-political and economic precariousness of the situation, the dream of attaining a luxurious lifestyle or having access to quality education often comes at a cost that is far beyond the reach of an average person. Therefore, students face numerous challenges during their crucial formative years. This study was carried out at the University of Sargodha (UOS) to explore the influence of socio-familial variables, such as age, gender, and family size, on academic achievement. Using a quantitative approach, a sample of 130 student teachers responded to the questionnaire. Boys in the nation had difficulty in terms of inflation and low income. This study employed a qualitative, descriptive research design that offers context for further study. The aim was to discover if school performance would be influenced by socio-familial factors. We carried out a survey in Medialuna involving 695 students from four middle and high schools. Data was analyzed using IBM SPSS version 26. The results showed that socio-familial factors had a weak positive relationship with academic performance. More research is needed to better understand ADHD and its treatment.